Biodiesel production using heterogeneous catalyst, application of Taguchi robust design and response surface methodology to optimise diesel engine performance fuelled with Jatropha biodiesel blends. Issue 1 (31st December 2022) - Singh, Aparna; Sinha, Shailendra; Choudhary, Akhilesh Kumar; Chelladurai, H.
Abstract : This study focusses on the production of biodiesel from JCO through the transesterification process using a heterogeneous catalyst. Biodiesel produced has been blended with diesel in different proportions by volume and performance has been experimentally assessed on a single cylinder engine. Engine input parameters such as FIP, CR, fuel blend and load have been optimised to achieve the optimum performance. For the investigation, Taguchi's robust design experimental procedure has been adopted. Experiments were conducted as per L18 orthogonal array to determine the rank and contribution of each input parameter on engine performance. At an ideal configuration of 17.98 CR, 269.96 bar FIP and 12 Kgf load using RSM, the maximum BP and BTHE have reached at 3.3 KW and 32.94%. The validation of RSM results was done and the percentage error was found to be 0.93% and 1.58% for BP and BTHE respectively. Abbreviations: B0: Diesel; B10: 10% Biodiesel blending; B20: 20% Biodiesel blending; B30: 30% Biodiesel blending; B40: 40% Biodiesel blending; B50: 50% Biodiesel blending; VCR: Variable compression ratio; BP: Brake power; BTHE: Brake thermal efficiency; CR: Compression ratio; FIP: Fuel injection pressure; RSM: Response surface methodology; JCO: Jatropha curcas oil; CI: Compression ignition; CCFCD: Centre composite face centred design; FFA: Free fatty acids; CaO: Calcium oxide; DOE: Design of experiments; ANOVA: Analysis of variance; S/N ratio: Signal to noise ratio